Evaluation of parameters extracted from tissue residue functions in dynamic susceptibility contrast MRI: Healthy volunteers examined during normal breathing and spontaneous hyperventilation - Ronnie Wirestam; Arthur Chakwizira; Peter Reinstrup (Heliyon)
Dynamic susceptibility contrast magnetic resonance imaging (DSC-MRI) is the most common MRI method in clinical environments for assessment of perfusion-related parameters. In this study, special emphasis was placed on the shape of the tissue residue function under different physiological conditions. DSC-MRI-based parameters assumed to reflect arterial delay and cerebral oxygen extraction were obtained by deconvolution of tissue and arterial contrast-agent concentration time curves. The established mean transit time (MTT) estimate was supplemented by biophysical modelling for extraction of the oxygen extraction capacity, quantified in terms of an apparent oxygen extraction fraction (AOEF) index. Eight healthy volunteers were examined during normal breathing and spontaneous hyperventilation. Whole-brain MTT and AOEF increased during hyperventilation in all volunteers (average increase 33 % and 30 %, respectively). The arterial delay, reflecting the inverse of arterial flow rate, was also prolonged in all volunteers, and the mean arterial delay was 63 % longer during hyperventilation. The corresponding whole-brain MTT estimates were 3.8 ± 0.7 s during normal breathing and 5.0 ± 1.3 s during hyperventilation (mean ± SD, n = 8). The applied Bézier curve deconvolution algorithm returned tissue residue functions of plausible shapes, i.e., without oscillations and negative values, and some indications that curve shape is relevant for improved assessment of oxygen extraction properties were demonstrated.